Pendampingan Pelatihan Pembukuan Sederhana bagi Pelaku UMKM di RW 05 Kelurahan Bareng Kecamatan Klojen Malang - Pudji Lestari; M. Hasyim Ashari; Hardi Susilo; Made Iska Aprilita Wardani; Mohammad Rofiudin; Novy Karmelita (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
MSMEs are the backbone of the Indonesian economy. To maintain the continuity of their business, MSMEs must have good and correct financial report management. MSME financial reports tend to be simple and ignore financial administration rules. This research aims to create and compile financial reports in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) for the Berkah Laris Frozen Food UMKM in Malang. The method used in this research is a descriptive qualitative method. The data sources used are primary data in the form of interviews and secondary data in the form of documentation. The results of the research are the presentation of an income statement showing operating profit, a change in capital report showing capital at the end of 2024, a financial position report showing the amount of assets owned equal to the total of liabilities and capital, and notes to the financial report which presents a general overview, an overview of important accounting policies, retained earnings and sales revenue for the period 31 December 2024.